PENEGAKAN HUKUM TERHADAP PELANGGARAN PARKIR KENDARAAN DI TEMPAT UMUM DITINJAU DARI PERATURAN DAERAH NOMOR 13 TAHUN 2016 TENTANG PENYELENGGARAAN PERHUBUNGAN DI KOTA DENPASAR - Setyawati, Ni Kadek Mita; Artajaya, I Wayan Eka (Jurnal Hukum Mahasiswa, 2024)
Fraudulent parking is an illegal or unofficial standing parking activity accompanied by unilateral recognition of the parking space. Therefore, the Denpasar City Government issued Regional Regulation Number 13 of 2016 concerning Transportation Management which regulates parking fraud. The problem formulation in this research is: 1) How is the law enforced against parking violations in Denpasar City based on Regional Regulations? And 2) What are the obstacles encountered in law enforcement against vehicle parking violations in Denpasar City? The type of research used is empirical legal research. Law enforcement is not yet optimal because there are still many obstacles from internal factors and external factors.